2009
DOI: 10.1172/jci37175
|View full text |Cite
|
Sign up to set email alerts
|

Wnt inhibitory factor 1 is epigenetically silenced in human osteosarcoma, and targeted disruption accelerates osteosarcomagenesis in mice

Abstract: Wnt signaling increases bone mass by stimulating osteoblast lineage commitment and expansion and forms the basis for novel anabolic therapeutic strategies being developed for osteoporosis. These strategies include derepression of Wnt signaling by targeting secreted Wnt pathway antagonists, such as sclerostin. However, such therapies are associated with safety concerns regarding an increased risk of osteosarcoma, the most common primary malignancy of bone. Here, we analyzed 5 human osteosarcoma cell lines in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
232
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(242 citation statements)
references
References 68 publications
(86 reference statements)
10
232
0
Order By: Relevance
“…These results are consistent with the in vitro observations that WIF1 overexpression does not interfere with normal cell growth of primary osteoblasts (Kansara et al, 2009) and HEK293 cells (data not published). Moreover, the use of peritumoral injection has the selective advantage of treating tumors with WIF1 at the tumor site, while avoiding the potential side effects at undesired target tissues often associated with systemic therapeutic strategies.…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachansupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the in vitro observations that WIF1 overexpression does not interfere with normal cell growth of primary osteoblasts (Kansara et al, 2009) and HEK293 cells (data not published). Moreover, the use of peritumoral injection has the selective advantage of treating tumors with WIF1 at the tumor site, while avoiding the potential side effects at undesired target tissues often associated with systemic therapeutic strategies.…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachansupporting
confidence: 92%
“…This inhibition of cell proliferation is consistent with the in vitro inhibition of cell growth by WIF1 as previously shown for other cancer cell lines (Ai et al, 2006;Kim et al, 2007;Kansara et al, 2009;Kawakami et al, 2009;Tang et al, 2009). However, in previous studies, WIF1 overexpression was shown to induce G 1 arrest in HPVimmortalized osteoblasts and osteosarcoma cell lines containing null or wild-type p53 (Kansara et al, 2009), as well as in bladder cancer cell lines containing mutant p53 (Tang et al, 2009). In contrast, our data show that in cervical cancer cells, which express very low levels of wild-type p53, WIF1 re-expression led to a significant increase in p53 expression, and induced cell-cycle arrest at G 2 /M and extensive apoptosis.…”
Section: Wif1 Inhibits Cervical Cancer Growth and Invasion I Ramachansupporting
confidence: 90%
See 1 more Smart Citation
“…Epigenetic silencing of sFRP promoters by hypermethylation is seen in colorectal and breast cancers (66,69). Wnt inhibitory factor-1, another secreted Wnt inhibitor, is silenced in several tumor types (73)(74)(75). Profiling the expression of Wnt antagonists or epigenetic marks associated with their silencing, while challenging in clinical practice, could be useful to predict sensitivity of tumors to upstream Wnt inhibitors.…”
Section: Genes Whose Decreased Expression Suggests Increased Wnt Signmentioning
confidence: 99%
“…(24)(25)(26)(27)(28) It has been noted that Wnt inhibitory factor 1 is epigenetically silence in human osteosarcomas, with targeted disruption in mice accelerating osteosarcoma development. (29) With the existing available data, it appears likely that the Wnt signaling pathway has an important role in osteosarcoma, but it is unclear whether up-or downregulation promotes its formation and malignant behavior.…”
Section: Etiology Of Osteosarcomamentioning
confidence: 99%